Current Management of Venous Diseases (Springer International Publishing, 2018)
This text provides an overview of venous diseases and focuses on clinical evaluation and management. It is intended to guide the treating physician by summarizing the evidence, giving technical tips, and outlining algorithms for common conditions. A unique feature of this book is clinical pearls given by experts in the field that are highlighted in each chapter. The first section of the book describes the essential anatomy and physiology/pathophysiology. It also includes evaluation of common presentations of venous diseases such as extremity edema and lower extremity ulceration with a summary for work up that includes conditions that can mimic venous diseases. The organization of the book follows the basic pathophysiology of venous disorders with chapters addressing special conditions of common interest such as pelvic congestion syndrome, thoracic outlet syndrome, and May-Thurner syndrome. There is emphasis on novel treatment modalities and emerging technologies through dedicated chapters to anticoagulant agents, emerging modalities to treat superficial venous reflux and venous stent technology. Finally, this book is a melting pot for physicians who have shown dedication and passion to the care of patients with venous disease regardless of specialty and location.The authors are an international panel of vascular experts who trained in vascular surgery, interventional radiology, interventional cardiology, hematology, pulmonology and critical care medicine. Therefore, the book will be of great value to the physicians and trainees in those specialties and to any person interested in developing in depth knowledge of the management of venous diseases.